1978
DOI: 10.1152/jn.1978.41.3.692
|View full text |Cite
|
Sign up to set email alerts
|

Auditory nerve fiber response to wide-band noise and tone combinations

Abstract: 1. Responses of single auditory nerve fibers to combinations of noise and tone were obtained. The results were found to depend on the relative effectiveness of each stimulus when presented alone. 2. When the response rate to one stimulus presented alone was considerably greater than the response rate to the other stimulus presented alone, the more effective stimulus dominated the responses when the two stimuli were combined. The more effective stimulus captured the response of the neuron. Thus, intense noise w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(36 citation statements)
references
References 0 publications
4
31
1
Order By: Relevance
“…Synchrony information is generally robust across a wide range of sound levels, even in response to signals in the presence of noise (Rhode et al, 1978). However, the temporal responses related to the envelope of the vowel complex would be expected to change as noise level increases, because the bandwidth of the peripheral filters increases with sound level and because adaptation shapes the responses of AN fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Synchrony information is generally robust across a wide range of sound levels, even in response to signals in the presence of noise (Rhode et al, 1978). However, the temporal responses related to the envelope of the vowel complex would be expected to change as noise level increases, because the bandwidth of the peripheral filters increases with sound level and because adaptation shapes the responses of AN fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The IPD thresholds and FMDTs were measured in quiet as well as in continuous noise backgrounds in order to test the robustness of the TFS processing to interfering noise. Physiological animal studies ͑e.g., Rhode et al, 1978;Abbas, 1981;Costalupes, 1985͒ have shown that phase locking to tones in the presence of background noise is generally preserved at SNRs near behavioral detection thresholds but ceases at sufficiently low SNRs. However, as no comparable studies exist in impaired hearing, it cannot be excluded that hearing impairment might potentiate the susceptibility of phase locking to noise disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…For auditory nerve (AN) fibers and most cochlear nucleus (CN) neurons, average discharge rate increases monotonically with tone level. However, the dynamic range of most AN fibers and CN neurons for rate encoding is significantly reduced by the presence of background noise (Geisler and Sinex 1980;Gibson et al 1985;Rhode et al 1978;Young and Barta 1986). This decrease is caused by a reduction in maximum rate at high tone levels and increased rates in response to the noise alone (Gibson et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The most intensively studied temporal property is the synchronization coefficient of discharges to tone frequency, which has been shown to yield lower detection thresholds than discharge rates in both AN fibers (Rhode et al 1978) and CN neurons (Miller et al 1987) at relatively high noise levels. However, neural mechanisms that can extract phase-locking information for tone-in-noise detection are unclear.…”
Section: Introductionmentioning
confidence: 99%